2016
DOI: 10.2337/db15-0661
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabonomic Profiling of Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the most common microvascular complication of diabetes and the leading cause of visual impairment in working-age adults. Patients with diabetes often develop DR despite appropriate control of systemic risk factors, suggesting the involvement of other pathogenic factors. We hypothesize that the plasma metabolic signature of DR is distinct and resolvable from that of diabetes alone. A nested populationbased case-control metabonomic study was first performed on 40 DR cases and 40 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 52 publications
(71 reference statements)
6
106
1
Order By: Relevance
“…Several recent studies of erythritol loading reported no effect on glucose (32,33), consistent with our findings. A study in patients with diabetes reported that erythritol and enrichment of another PPP biomarker (ribose) were increased in patients with diabetic retinopathy, and suggested that polyol pathway flux may yield biomarkers of clinical risk in diabetes (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies of erythritol loading reported no effect on glucose (32,33), consistent with our findings. A study in patients with diabetes reported that erythritol and enrichment of another PPP biomarker (ribose) were increased in patients with diabetic retinopathy, and suggested that polyol pathway flux may yield biomarkers of clinical risk in diabetes (34).…”
Section: Discussionmentioning
confidence: 99%
“…[22],[23],[24]. Metabolomics of human plasma has been used to characterize diabetic retinopathy[25],[26], open angle glaucoma[27] and anterior uveitis. [28] In AMD, investigators have used untargeted LC-MS metabolomics to investigate changes in the plasma of “wet” AMD patients (n = 26), compared to controls (n = 19).…”
Section: Introductionmentioning
confidence: 99%
“…In ophthalmology, metabolomics has been used to study various eye diseases including glaucoma [10][11][12][13][14][15][16] , age-related macular degeneration [17][18][19] , diabetic retinopathy [20][21][22] , keratoconus [23] , refractive error [24,25] , retinal detachment [26] , uveitis [27,28] , dry eye [29,30] , and other ocular surface diseases [31] . Analyses have been performed on tear fluid [23,[29][30][31][32] , aqueous humor [24,25,33,34] , vitreous humor [20,26,27,35,36] , cornea [37][38][39] , conjunctiva [40] , and lens [41,42] samples.…”
Section: Metabolomics In Ophthalmologymentioning
confidence: 99%